Guilt without conviction – impunity of the psycho-manipulator - Łukowski, Piotr (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
Many outstanding psychologists like Philip Zimbardo and Simon Baron-Cohen ask the fundamental question: How Can Good People Turn Evil? An answer to this question should also be interesting and important for lawyers. In fact, sometimesthere are situations when the so called, ‘good people’ become capable of committing real crimes. Some of these situations are not accidental, but they are created by somebody who knows well methods how to manipulate others. Then, we usually have a case ofguilt without conviction.